2010
DOI: 10.3109/10826080903499562
|View full text |Cite
|
Sign up to set email alerts
|

Early Motivation, Well-being, and Treatment Engagement of Chronic Substance Users Undergoing Treatment in a Therapeutic Community Setting

Abstract: This study explored the predictors, role and effects of motivation in chronic substance users as they began residential treatment, using the Self-Determination Theory (SDT) framework. Testing of the SDT model involved a sample of 350 clients from six therapeutic communities across Australia who completed a battery of standardized measures. It was hypothesized that clients with a more autonomous motivational attitude toward treatment would be more likely to engage in the therapeutic process and would report mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 39 publications
3
36
1
Order By: Relevance
“…'Say yes' appears to relate to commitment, motivation, or intentions for treatment (e.g. Dowling & Cosic, 2011;Klag et al, 2010). 'Be A C C E P T E D M A N U S C R I P T…”
Section: The Service Engagement Scale (Ses)mentioning
confidence: 99%
See 2 more Smart Citations
“…'Say yes' appears to relate to commitment, motivation, or intentions for treatment (e.g. Dowling & Cosic, 2011;Klag et al, 2010). 'Be A C C E P T E D M A N U S C R I P T…”
Section: The Service Engagement Scale (Ses)mentioning
confidence: 99%
“…Motivation (Dingle et al, 2008), intentions (Klag et al, 2010) or commitment (Joe et al 1999) to participate, rather than the acts of participation, have been employed as proxies for engagement. Motivation can predict behavior (Chatzisarantis, Hagger, Smith, & Sage, 2006) and has thus been conceptualized by some researchers (e.g.…”
Section: Engagement As Participation or Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who dropped out were significantly more likely to have a criminal history (consistent with the findings of Darke et al, 2012 (Cardoso, Chan, Berven, & Thomas, 2003), spirituality (Dermatis et al, 2010), and engagement and motivation (Klag, Creed, & O'Callaghan, 2010). Five studies included two time points with the gap between measured points varying in length from 4 -15 months post program completion, and were in pre and post format (Bankston et al, 2009;Dekel et al, 2004;López-Goñi et al, 2010;Messina et al, 2000;Zoccali et al, 2007).…”
Section: Retention and Dropout As Well As Mean Length Of Stay In Treasupporting
confidence: 50%
“…One study (Klag et al, 2010) tested the self-determination theory in relation to the Therapeutic Community and found that, as hypothesized, higher levels of autonomy led to higher reports of psychological well-being during the early stages of rehabilitation, and higher levels of engagement in the rehabilitation process. Dermatis, Salke, Galanter, and Bunt (2001) investigated social affiliation (a feature of the community-as-method approach), and depression.…”
Section: Psychological Constructs Measuredmentioning
confidence: 99%